EIS Study on the Electrode-Separator Interface Lamination - Martin Frankenberger; Madhav Singh; Alexander Dinter; Karl-Heinz Pettinger (Batteries, 2019)
This paper presents a comprehensive study of the influences of lamination at both electrode-separator interfaces of lithium-ion batteries consisting of LiNi1/3Mn1/3Co1/3O2 cathodes and graphite anodes. Typically, electrode-separator lamination shows a reduced capacity fade at fast-charging cycles. To study this behavior in detail, the anode and cathode were laminated separately to the separator and compared to the fully laminated and non-laminated state in single-cell format. The impedance of the cells was measured at different states of charge and during the cycling test up to 1500 fast-charging cycles. Lamination on the cathode interface clearly shows an initial decrease in the surface resistance with no correlation to aging effects along cycling, while lamination on both electrode-separator interfaces reduces the growth of the surface resistance along cycling. Lamination only on the anode-separator interface shows up to be sufficient to maintain the enhanced fast-charging capability for 1500 cycles, what we prove to arise from a significant reduction in growth of the solid electrolyte interface.